Occupational Health and Safety (OHS) Hazard Risk Control Strategies in Construction Projects: A Literature Review - Yayu Angriani (Borneo Scientific Publishing, 2025)
The construction industry is one of the sectors with the highest rate of work accidents, mainly due to the failure to identify and control risks effectively. This study aims to examine the Occupational Safety and Health (OHS) risk control strategy in piling work in the Section IV construction project using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. The identification results show that there are 55 potential hazards classified into three risk categories: high, medium, and low, with the dominance of non-technical internal risk factors such as HR behavior and completeness of project information. The control strategy is implemented in stages based on the risk control hierarchy, including engineering, administrative control, and the use of Personal Protective Equipment (PPE), and is supported by ongoing training and the use of technology such as Virtual Reality (VR) and the Internet of Things (IoT). Obstacles in implementing this strategy are mainly found in the Small and Medium Enterprises (SMEs) sector which has limited resources. Therefore, managerial commitment, policy support, and adequate funding are needed to ensure the effectiveness of OHS management and the achievement of the zero accident target.